A comparative and prospective study of two different radiation fractionation schedules with concurrent chemotherapy in locally advanced head-and-neck squamous cell carcinoma - Chayan Roy; Linkon Biswas; Arabinda Roy; Sharma, Shyam; Firdoushi Khatun; Srikrishna Mandal (Asian Journal of Medical Sciences, 2022)
Background: Accelerated fractionation radiotherapy has radiobiological advantage of preventing accelerated tumor repopulation and logistic advantage of treating more patients than conventionally fractionated radiotherapy because of its relatively shorter treatment duration. Aims and Objectives: In this study, we compared accelerated fractionation with conventionally fractionated radiotherapy in terms of tumor response and acute toxicities for the treatment of locally advanced head-and-neck carcinomas. Materials and Methods: Patients with Stage III and IVA carcinoma of head-and-neck region were randomized into two groups. The study group patients received accelerated radiotherapy to a total dose of 66Gy in 33 fractions, 2Gy/fraction, 6 fractions/week over a time period of 5.5 weeks. Control group received conventionally fractionated radiotherapy to same total dose and fraction size but 5 fractions/week, over a time period of 6.5 weeks. Both groups received concurrent weekly Cisplatin. All patients were followed up weekly for treatment related acute toxicity during the treatment and then at every month for 6 months after completion of treatment. Results: About 26.6% patients of study arm achieved complete response in comparison to 25.6% of control arm, but the difference was not statistically significant (P=0.957). Although statistically not significant, higher grade of skin toxicity (60%vs.35%, P=0.179) and xerostomia (46% vs. 29%, P=0.155) was also numerically higher in accelerated fractionation. Conclusion: For locally advanced head-and-neck carcinoma, accelerated fractionation radiotherapy with concurrent chemotherapy can be considered as an acceptable and effective alternative of conventionally fractionated concurrent chemoradiotherapy in terms of treatment response and acute toxicity profile.